TATA KELOLA DAN PENINGKATAN DAYA SAING EKONOMI: SUATU PENULUSURAN KONSEP - Maxensius Tri Sambodo (Jurnal Ekonomi dan Pembangunan, 2025)
This paper aimed to develop a conceptual framework that connect between governance and competitiveness. Governance needs to exploite and develop, supreme charactheristics of economic community within government, business sector, and society in the context of global, central and local government. We defined this framework as proper governance. Proper governance in the context of competitiveness aims to promote inclusiveness and cooperative. Proper governance is optimal combinations among elements of proper governance such as developmentalist, democratic, socially inclusve, and local content; and the elements of competitiveness such as trust and confidence, gradual, balance, and specific, and cooperative and collaborative. Thus, proper governance in the context of competitivenss needs to develop inclusive development within the spirit of cooperative or gotong royong.